The Evolution of Management Theory: A Literature Review : Evolusi Teori Manajemen: Sebuah Tinjauan Literatur - Djalilov Jakhongir (Universitas Muhammadiyah Sidoarjo, 2025)
The evolution of management principles is evaluated throughout this review through an examination of their historical progression starting from pre-industrial times up to modern theories. The research emphasizes traditional management theories by linking Taylor’s Scientific Management and Fayol’s Administrative Principles to modern behavioral theories including Human Relations Movement and Maslow’s Hierarchy of Needs and McGregor’s Theory X and Theory Y. The research investigates strategic management frameworks especially Porter’s Five Forces and the Resource-Based View in detail to determine their capacity to resolve organizational difficulties. This analysis explores both the timeless value of management principles and the requirement to adjust them according to current global market shifts alongside technology progress and temporary staffing practices. The multidimensional evaluation demonstrates to both academic researchers and organizational professionals how management grew in the past while providing approachable methods to resolve present-day organizational intricacies. Highlights: Historical evolution: From pre-industrial management to modern theories. Key frameworks: Scientific Management, Administrative Principles, Behavioral Theories, Strategic Models. Relevance today: Adapting principles to global markets, technology, and staffing trends. Keywords: Management evolution, classical theories, modern management, scientific management, organizational behavior, management practices, managerial trends.